2017
DOI: 10.1007/s00394-017-1567-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of dietary interventions for gestational weight gain and gestational diabetes in overweight and obese pregnant women

Abstract: PurposeThe number of overweight and obese women is increasing in the obstetric population. The aim of this study was to review studies that reported results related to the efficacy of dietary interventions on gestational weight gain (GWG) or the prevention of gestational diabetes (GDM) in overweight and obese women.MethodsThe search was performed using the CINAHL, PubMed, Scopus and Medic electronic databases and limited to the years between 2000 and March 2016. This systematic review includes 15 research arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…According to the Institute of Medicine, the recommend GWG for overweight pregnant women is 7–11.9 kg and for obese pregnant women is 5–9 kg [ 48 ]. Dietary interventions and physical activity interventions were recommended to limit GWG and prevent GDM in overweight and obese pregnant women [ 49 , 50 , 51 ]. However, a randomised controlled trail in UK found that dietary and physical interventions in pregnant women with obesity were not adequate to prevent GDM or large-for-gestational-age infants, and a recent study in Australia also reported no significant differences in GDM between the behavioural nutrition intervention group and the control group after adjusting confounding factors [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Institute of Medicine, the recommend GWG for overweight pregnant women is 7–11.9 kg and for obese pregnant women is 5–9 kg [ 48 ]. Dietary interventions and physical activity interventions were recommended to limit GWG and prevent GDM in overweight and obese pregnant women [ 49 , 50 , 51 ]. However, a randomised controlled trail in UK found that dietary and physical interventions in pregnant women with obesity were not adequate to prevent GDM or large-for-gestational-age infants, and a recent study in Australia also reported no significant differences in GDM between the behavioural nutrition intervention group and the control group after adjusting confounding factors [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their systematic review, Lammimpaa and coauthors concluded that variability in the delivery of dietary interventions is a key factor affecting study outcomes in GDM. Thus, additional research on the benefits of dietary CHO, with or without other nutritional factors, should also pay attention to the consistency of its delivery [70].…”
Section: Role Of Dietary Carbohydrates In Gdmmentioning
confidence: 99%
“…The precise underlying mechanisms between pre-pregnancy and early pregnancy DPs with the risk of GDM, however, remains to be elucidated. Nevertheless, the available evidence seems to support that women planning for pregnancy or in early pregnancy should be the target of lifestyle intervention for preventing GDM [60][61][62].…”
Section: Pre-pregnancy Bmimentioning
confidence: 99%